2021
DOI: 10.3390/cancers13174329
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Extrathoracic Malignant Tracheoesophageal Fistula—A Differentiated Reconstructive Algorithm

Abstract: Background: Tracheoesophageal fistulae (TEF) after oncologic resections and multimodal treatment are life-threatening and surgically challenging. Radiation and prior procedures hamper wound healing and lead to high complication rates. We present an interdisciplinary algorithm for the treatment of TEF derived from the therapy of consecutive patients. Patients and methods: 18 patients (3 females, 15 males) treated for TEF from January 2015 to July 2017 were included. Two patients were treated palliatively, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…The results were highly similar to the findings in the literature [ 20 ]. The TPR of esophagography, bronchoscopy, and multidetector row spiral CT in 10 cases of H-TEF were 83%, 72.1%, and 20.0%, respectively, which showed that the TPR of esophagography and bronchoscopy was relatively higher and most patients could be diagnosed through these two techniques [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results were highly similar to the findings in the literature [ 20 ]. The TPR of esophagography, bronchoscopy, and multidetector row spiral CT in 10 cases of H-TEF were 83%, 72.1%, and 20.0%, respectively, which showed that the TPR of esophagography and bronchoscopy was relatively higher and most patients could be diagnosed through these two techniques [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the majority of patients die from recurrent aspiration pneumonias in the long run. 24 Individual fistula prostheses represent an ultima ratio treatment option in difficult to treat TEF.…”
Section: Discussionmentioning
confidence: 99%
“…According to the presented data as well as clinical experience, these restrictions can last for months and years. Unfortunately, the majority of patients die from recurrent aspiration pneumonias in the long run 24 . Individual fistula prostheses represent an ultima ratio treatment option in difficult to treat TEF.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are reports of improved survival [ 13 , 14 ], stenting remains a palliative treatment, and its disadvantages are the possibility of fistula enlargement and the difficulty of surgical manipulation due to stenting. Surgery may be an option, but most patients undergo esophageal bypass surgery [ 15 , 16 ] or muscle flap coverage [ 9 , 17 ] as palliative treatments. There are reports of two-step surgery for TEF caused by lung cancer [ 18 ] and TEF caused by malignant lymphoma that was closed after continued chemotherapy [ 19 ], but we were unable to find any reports of radical surgery for TEF caused by esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%